2006
DOI: 10.1111/j.1462-2920.2006.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

A new α‐proteobacterial clade of Bdellovibrio‐like predators: implications for the mitochondrial endosymbiotic theory

Abstract: Bdellovibrio-and-like organisms (BALOs) are peculiar, ubiquitous, small-sized, highly motile Gram-negative bacteria that are obligatory predators of other bacteria. Typically, these predators invade the periplasm of their prey where they grow and replicate. To date, BALOs constitute two highly diverse families affiliated with the delta-proteobacteria class. In this study, Micavibrio spp., a BALO lineage of epibiotic predators, were isolated from soil. These bacteria attach to digest and grow at the expense of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 59 publications
(82 reference statements)
3
79
0
1
Order By: Relevance
“…This, along with the examination of their genomic content and genome structure, suggests that epibiotic predation in BALO results from convergent evolution, and has evolved a number of times in unrelated taxa. Furthermore, M. aeruginosavorus represents a deep taxonomic branch in the a-proteobacteria with its closest relative within the SAR116 group, both forming a sister clade to the Rhodospirillales (Davidov et al, 2006;Wang et al, 2011). Because neither the SAR116 nor the Rhodospirillales contain any known predators, it is likely that M. aeruginosavorus evolved to be an epibiotic predator 'de novo', from an unidentified nonpredatory ancestor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, along with the examination of their genomic content and genome structure, suggests that epibiotic predation in BALO results from convergent evolution, and has evolved a number of times in unrelated taxa. Furthermore, M. aeruginosavorus represents a deep taxonomic branch in the a-proteobacteria with its closest relative within the SAR116 group, both forming a sister clade to the Rhodospirillales (Davidov et al, 2006;Wang et al, 2011). Because neither the SAR116 nor the Rhodospirillales contain any known predators, it is likely that M. aeruginosavorus evolved to be an epibiotic predator 'de novo', from an unidentified nonpredatory ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…M. aeruginosavorus strain EPB was isolated from saline soil in Israel using Pseudomonas corrugata as prey (Davidov et al, 2006). The prey strains were cultured in PYE and NB, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The Δ-Proteobacteria represented approximately 4% of Proteobacteria and belonged predominantly to the class Bdellovibrionales. None of the sequences could be assigned to a family, but they did have high similarity with order members thought to be predators (Davidov, Huchon, Koval, & Jurkevitch, 2006).…”
Section: Aquatic Science and Technologymentioning
confidence: 99%
“…15 Bdellovibrio-like α-proteobacterial predators have been recently discovered, and it has been suggested that this might have implications for the origin of mitochondria. 99 In our view selfish α-proteobacterial parasites had the ability to disrupt pre-karyotes' membranes. 15 Under this selective pressure the pre-karyote evolved various mechanisms to resist the aggressive infection of α-proteobacterial parasite.…”
Section: Novel Hypothesis For the Origin Of Eukaryotesmentioning
confidence: 99%